La abundancia de galaxias y halos de materia oscura en el universo CDM - Abadi, Mario Gabriel (2013)
Abstract: We use the GIMIC cosmological hydrodynamical simulations to perform a study of the properties of spheroidal galaxies formed without merger events. We select a sample of galaxies with stellar mass greater than 10 M and we classified them according to the degree of rotation support through the ratio of the rotational kinetic energy respect to the total at redshift z=0. Taken only those with ; we focus on those with accreted mass fraction less than 20 to ensure that they are merger free. We found that these spheroidal galaxies have stellar mass M M and have an important barred component. Interestingly; we found that in many cases the simulated galaxies present two external rings around the bar being both coplanar and counter-rotating to each other. FULL TEXT IN SPANISH